Assessment of Antinutrient Properties of Selected Fruit Peels - Alza, Ammabel Oclarit; Rosario, Romeo Macaltao Del; Fajardo, Maria Teresa Mabaylan (Asian Journal of Biological and Life Sciences, 2025)
Purpose: The study examined the anti-nutritional composition of four distinct fruit peels and assessed whether these discarded peels retain bioactive substances that have potential health benefits. Materials and Methods: Antinutrient analysis was conducted on each extract obtained from the peelings to assess the health consequences of their utilization or absence. The chosen fruit peels, specifically avocado, jackfruit, mango paho, and pineapple, were obtained from the local markets of Cagayan de Oro. The Tukey Method was used for statistical comparisons of fruit peel combinations. Results: The alkaloid concentration of mango paho peels was the highest among the studied fruit peels, measuring 1.0802+0.185. The differences between all fruit peel pairs were statistically significant, with values exceeding the critical threshold of 0.05. Pineapple peels had the greatest oxalate concentration at 6.2297+0.060, while avocado peels contained only 0.41162+0.057. The comparison of pineapple peel with other fruit peels demonstrated a significant difference according to the Tukey Method. All combinations of fruit peels showed statistically significant differences, with p-values higher than the crucial value of 0.05. Phytate levels in the fruit peels were extremely low, with avocado and jackfruit peels having the lowest average values of 0.2441 and 0.2477, respectively. The average phytate concentration of mango paho was 0.4774. Mango paho had the highest saponin concentration at 5.5385, while avocado peel had the lowest quantity at an average of 1.8236. There was no notable variation in the alkaloid and total saponin levels among the chosen fruit peels. However, there was a considerable difference in their oxalate and phytate levels. Conclusion: The study recommends assessing the antioxidant capacity of the chosen fruit peels, as these peels have been found to contain antinutrient compounds that are harmless for human consumption. Further, each fruit peel can be tested for cytotoxicity levels to ensure safety for animal consumption and to prevent allergic or toxic reactions.
Keywords: Alkaloids; Antinutrient; Fruit Peels; Oxalates; Phytate; Saponin